2022
DOI: 10.3389/fsurg.2022.893977
|View full text |Cite
|
Sign up to set email alerts
|

N7-Methylguanosine Regulatory Genes Profoundly Affect the Prognosis, Progression, and Antitumor Immune Response of Hepatocellular Carcinoma

Abstract: BackgroundHepatocellular carcinoma (HCC) is a common abdominal cancer with poor survival outcomes. Although there is growing evidence that N7-methylguanosine (m7G) is closely associated with tumor prognosis, development, and immune response, few studies focus on this topic.MethodsThe novel m7G risk signature was constructed through the Lasso regression analysis. Its prognostic value was evaluated through a series of survival analyses and was tested in ICGC-LIRI, GSE14520, and GSE116174 cohorts. CIBERSORT, ssGS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 44 publications
0
4
0
Order By: Relevance
“…Previous studies found m7GRGs expression in ovarian cancer (OC) is significantly correlated with immune cells (involving CD4 + memory resting T cells, plasma cells, and Macrophages M1) (Zheng et al, 2022). In Hepatocellular carcinoma high m7G risk led to a decreased infiltration level of CD8 + T cells, whereas it increased the infiltration levels of Tregs and macrophages (Zhou et al, 2022). METTL1 expression was enhanced in HCC, accompanied by increased CD11b CD15 polymorphonuclear-myeloid-derived suppressor cells (PMN-MDSCs) and decreased CD8 T cells.…”
Section: Discussionmentioning
confidence: 94%
“…Previous studies found m7GRGs expression in ovarian cancer (OC) is significantly correlated with immune cells (involving CD4 + memory resting T cells, plasma cells, and Macrophages M1) (Zheng et al, 2022). In Hepatocellular carcinoma high m7G risk led to a decreased infiltration level of CD8 + T cells, whereas it increased the infiltration levels of Tregs and macrophages (Zhou et al, 2022). METTL1 expression was enhanced in HCC, accompanied by increased CD11b CD15 polymorphonuclear-myeloid-derived suppressor cells (PMN-MDSCs) and decreased CD8 T cells.…”
Section: Discussionmentioning
confidence: 94%
“…Transcribed mRNAs are bound and escorted to the cytoplasm by the CBC for further translation and modification 15,16 . It is, therefore, understandable that NCBP2 is highly expressed in various tumors, including lung cancer, and is associated with their poor prognosis 45,46 . However, whether NCBP2 has selectivity in term of mRNA translation is still largely unknown.…”
Section: Discussionmentioning
confidence: 99%
“…15,16 It is, therefore, understandable that NCBP2 is highly expressed in various tumors, including lung cancer, and is associated with their poor prognosis. 45,46 However, whether NCBP2 has selectivity in term of mRNA translation is still largely unknown. EIF4E1 functions based on m7G cap structure in cytoplasm.…”
Section: Discussionmentioning
confidence: 99%
“…Various prognostic models for m7G-related genes in lower-grade gliomas have emerged, however, the models are not well developed (Wang, Zhong et al 2022). Furthermore, m7G-related genes are directly and extensively correlated with tumor microenvironment and immune cells (Wu, Li et al 2022, Zhou, Yang et al 2022.…”
Section: Introductionmentioning
confidence: 99%